Psycho-social factors as correlates of conduct disorders among students with learning disabilities in Ibadan, Oyo State (2017)
This study examined the influence of two psycho-social variables namely: self-esteem and peer influence as correlates of conduct disorder among students with learning disabilities in lbadan, 0yo State. The descriptive survey research design of the correlational type was adopted for the study. Two hundred secondary school students were selected through purposive sampling techniques from five public secondary schools in Akinyele Local Government Area of lbadan, Oyo State. Three research questions were asked and answered. Screening Checklist for Suspected Learning Disability (r= 0.72), Adapted version of the Disruptive Behaviour Disorder (0.68), Rosenberg Self-Esteem (r = 0.83) scale and Peer Influence Questionnaire (r =0.89), were used for data collection. The data collected were analyzed using Pearson Product Moment Correlation and Multiple Regression tools. The results showed that self-esteem has significant relationship with conduct disorder (r =. 162; p (0.05) while peer influence has no significant linear correlation with conduct disorder among students with learning disabilities. It was also revealed that when both predictor variables (self-esteem and peer influence) are taken together, they significantly predict respondents' conduct disorder (F(3/196, =10.901, p<0.05); R2 adj. =. 130. Furthermore, the findings showed that the two independent variables contributed differently to the prediction of respondents' conduct disorder with the most significantly potent contributor to conduct disorder being self-esteem (t= 2.018; P< 0.05) followed by peer influence (t=-,497, P<O.O5). On the basis of the findings of the study it was recommended that teachers of students with LD and comorbid conduct disorder should endeavour to present activities that boost self-esteem to the students to avoid a lowered seIf-esteem and high display of CD in school. Students with LD should be encouraged to express their feelings without any form of fear or intimidation by their parents and teachers. They should also be trained on how to manage their emotions.